ASSETMANAGEMENTIN HISTORIC BUILDINGS CONSERVATION: CASE OFBRAGA AREABANDUNG - AKBAR, ROOS (ITB Journal Publisher, LPPM ITB, 2010)
This paper tries to explore the initial possibility of asset management in managing assets governed by the local government. In this research, historic building assets conservation is treated as a model in implementing asset management. Asset management model is implemented in many places in managing infrastructure network, but has never been implemented in historic building management in Indonesia. Quite different than any other modeling in general, the case for historic building should iteratively relate to the characteristics and issues of historic buildings and any management opportunities that can be done by the government as the responsible party in managing historic buildings. Asset management implementation in this research initiated with identifications of related attributes of the historic building assets based on available and applicable management possibilities. This paper shall not explore the detail exposition of each attributes found, but the approach that is implemented through asset management which shows comprehensive understanding on this issue of historic building management.The effort of understanding the issues and types of management that is possible in historic building that then may give rise to the identification attributes of this issue that shall be the start of asset management implementation for historical buildings based on information system. It is also understood that this study may be further developed especially in drilling down the attributes used prior to asset management model implementation.